Hubungan Pengetahuan Ibu Tentang Deteksi Dini Kanker Serviks dengan Motivasi Pemeriksaan IVA di Puskesmas Peureulak Aceh Timur Tahun 2024 - Ainil Mastura; Ester Simanullang (Inovasi Kesehatan Global, 2024)
Early detection is the use of certain tests, tests or procedures that can be used well to differentiate between a person who appears healthy or who is actually healthy and suffers from an abnormality, an attempt to prevent the disease from identifying a disease or disorder that is not clinically obvious. The purpose of this study is to determine the relationship between maternal knowledge about early detection of cervical cancer and IVA Test motivation at the Peureulak East Aceh Health Center in 2024. This study is quantitative with a cross sectional research design conducted in the working area of the Peureulak Health Center. The population in this study is married pregnant women, which is 96 people. The sampling technique used is total sampling. The instrument used was a questionnaire and bivariate analysis using the Chi Square test. The conclusion obtained was a p-value of 0.001<0.05, which means that there is a relationship between knowledge and motivation for early detection of cervical cancer at the Peureulak Health Center, East Aceh in 2024.